Association between handgrip strength, walking, agerelated illnesses and cognitive status in a sample of Portuguese centenarians - Pato, Maria Vaz (2020)
Abstract Background: Centenarians are a growing population in Europe and present significant variability in motor and cognitive functions. The aim of our study was to characterize health status, as well as cognitive and motor functions in a group of Portuguese centenarians. In addition, our study also aimed at analyzing the relationship between cognitive functions and the burden of diseases affecting the elderly. Methods: Fifty-two centenarians were evaluated using the Mini-Mental State Examination, short version. Walking- related parameters (velocity and time spent in the 3 m walk test), grip strength and number of age-related illnesses were also measured. The relationship between cognitive scores and time spent in the three metre walk test, velocity, grip strength and number of diseases was analysed. Results: Cognitive scores showed a positive correlation with both handgrip strength and time spent in the three metre walk. In contrast, no association was found between cognitive scores and the presence/absence of disease, walking velocity or number of diseases present. Conclusions: These results suggest that in centenarians, cognitive functions may be related with motor functions.